Deprotonation, Chloride Abstraction, and Dehydrohalogenation as Synthetic Routes to Bis‐Pyrazolate Pyridyl Iron(II) Complexes. Issue 34 (11th September 2017) - Cook, Brian J.; Polezhaev, Alexander V.; Chen, Chun‐Hsing; Pink, Maren; Caulton, Kenneth G.
Abstract : The process of removal of protons and chloride, dehydrohalogenation, from [(H2 L)FeCl2 ] is investigated systematically, to understand the reactivity of the implied transient LFe II . Reaction of [(H2 L)FeCl2 ] with 2 equiv. of LiN(SiMe3 )2 yields the "‐ate" complex LiClFe2 L2, as its dimer with every iron five‐coordinate in an FeN4 Cl environment. To avoid Li + cation derived from LiN(SiMe3 )2, reaction of Na2 L with FeCl2 gives a product from addition of water, paramagnetic Na2 [NaFe(HL)(L)]2 (LFeO), which reveals Na/pyrazolate Nβ interactions and a five coordinate oxo group in the OFe3 Na2 core of this aggregate. Abstraction of chloride in [(H2 L)FeCl2 ] with NaBArF4 in THF gives paramagnetic [(H2 L)Fe(THF)3 ] 2+, which fails to react with CO. Dehydrohalogenation in the presence of Ph2 PC2 H4 PPh2, dppe, gives both [LFe(κ 2 ‐dppe)]2 (µ‐dppe)] and [LFe(κ 2 ‐dppe)(κ 1 ‐dppe)], diamagnetic saturated species, which can be separated by pentane extraction. Dehydrohalogenation in the presence of t BuNC gives diamagnetic [LFe(CN t Bu)3 ]. This is selectively methylated at both pyrazolate β‐nitrogen atom to give [L Me Fe( t BuNC)3 ] 2+ which shows rich cyclic voltammetry, and which is reduced, with KC8, to diamagnetic [L Me Fe( t BuNC)2 ]. Structure determination of some of these, together with IR data on isocyanide stretching frequencies, show L 2– to be a stronger donor than L Me . First installing triflate (to avoid the more persistent chloride ligand) facilitates access to [LFe(Lewis base)3 ] 2+ complexes, but this cation still shows relatively weak binding of CO to LFe II, which implicates weak π basicity of that d 6 species. Production of paramagnetic bis ‐pincer complexes [(H2 L)2 Fe] 2+ and [(L Me )2 Fe] 2+ in the presence of abundant Lewis base in polar medium is demonstrated, which illustrates a pincer ligand redistribution challenge to be kept in mind when trying to maintain a 1:1 Fe:pincer ratio, for highest reactivity. Abstract : The removal of protons and chloride, dehydrohalogenation, from (H2 L)FeCl2 is investigated, to understand the reactivity of the implied transient LFe II . Collective evidence shows that divalent iron is not strongly obedient to the 18 electron rule, although Fe II is faithful to preferred coordination number 6; among all species reported here, only the Fe2 and Fe3 species have coordination number 5.